(untitled) (Journal of Geography and Environmental Management, 2021)
The study examined the low-water flow of the Ili River in the Kapshagai Gorge. Data on low-water water consumption for the period 1940-2015 were collected. Hydrographs of the low-water flow for typical years are constructed. As a result of the analysis of hydrographs, the dates of the onset and end of the low-water periods of the Ile River were clarified. As a result of the analysis of hydrographs built on the hydrological post located 37 km below the HPP, the months October-November for the winter period and December-March for the winter period were taken. The characteristics of the low-water flow for the autumn and winter low-water periods are calculated. It was revealed that after the construction of the Kapshagai reservoir along the Ili River, there was a change in the low-water flow. Therefore, the hydrological calculations of the characteristics of the low-water water flow were carried out separately for the period 1940-1971, when the conditional natural water regime of the Ile River was still observed, and for the period from 1971 to 2015, when there was an increase in the anthropogenic load on the flow of the river basin. For these periods, the statistical parameters of the low-water flow of autumn and winter low water were calculated. It is shown that during the period of increased anthropogenic load on the Ili River, the coefficient of variation of the low-water flow series of the autumn low – water period increased more than twice, and for the winter period – significantly. The values of 75-97% of the low-water consumption security were determined for each period separately. It is shown that the low-water flow of the Ili River has significantly decreased over the last period.